2008
DOI: 10.1007/s00068-008-8093-x
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel and Proximal Femoral Fractures: Does Timing of Surgery Affect Blood Loss and Length of Admission? A Preliminary Study Prior to Multicenter Trial

Abstract: Patients should be considered for early operation provided there are no additional bleeding risk factors, as although postoperative hemoglobin is lower, mortality and complication rates are similar, and length of admission is shorter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The odds ratio was non-significant at 0.44 (95% CI: 0.15-1.30). Cox et al [31] reported mean units transfused; this was non-significant between early and delayed surgery groups (p > 0.05).…”
Section: Blood Transfusionmentioning
confidence: 81%
See 3 more Smart Citations
“…The odds ratio was non-significant at 0.44 (95% CI: 0.15-1.30). Cox et al [31] reported mean units transfused; this was non-significant between early and delayed surgery groups (p > 0.05).…”
Section: Blood Transfusionmentioning
confidence: 81%
“…On meta-regression, neither mean age (p = 0.268) nor percentage female (p = 0.963) could predict differences in mortality. Three studies [31,55,58] reported mortality outcomes in early versus delayed surgery. Overall, the odds ratio for mortality was 0.61 (95% CI: 0.11-3.25).…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of hip fracture patients on antiplatelet medication in our study (approximately 3%) is comparable with others. 25 Owing to the small number of patients on antiplatelet medications, data had to be collected over three years. However, the number of such patients is likely to rise in the future.…”
Section: Study Limitationsmentioning
confidence: 99%